Penyuluhan Pencegahan Pernikahan Dini di MTS As`adiyah 28 Salopokko Desa Ugi, Kecamatan Sabbangparu, Kabupaten Wajo - Martono; Mustari; Andi Dadi Mashuri Makmur; Auliana Rezky Widyaningsih; Reski Aulia; Fatanah Nurul Muflihah; Ning Ainiyyah Magfirah (Compile Journal of Society Service, 2025)
This community service activity aims to increase knowledge about the impact of early marriage as a preventive measure against early marriage at MTS As'adiyah 28 Salopokko, Ugi Village, Sabbangparu District, Wajo Regency. Madrasah is an educational institution that focuses primarily on religious and moral education, so counseling on preventing early marriage at madrasah is expected to be an agent of change in preventing early marriage among adolescents with a religious approach in the future. This community service activity is carried out in three stages, namely the preparation stage, the implementation stage, and the reporting stage. The success of this community service activity is measured before and after the delivery of the material. The results of the reporting stage show an increase in students' knowledge regarding the prevention of early marriage.